Arthroscopic rotator cuff repair with manipulation under anesthesia yields similar clinical outcomes to isolated rotator cuff repair and is associated with lower retear rates in medium-sized tears - Yutaka Kinoshita; Yoshitsugu Takeda; Koji Fujii; Naoto Suzue; Yoshiteru Kawasaki; Junichiro Sumitomo; Kenichiro Kita; Yugen Fujii; Koichi Sairyo (Clinics in shoulder and elbow, 2025)
Background: The role of manipulation under anesthesia (MUA) without arthroscopic capsular release in patients with preoperative stiffness undergoing arthroscopic rotator cuff repair (ARCR) remains unclear. Additionally, the association between shoulder stiffness and tendon healing after ARCR is still controversial. This study aimed to compare the clinical outcomes and retear rates between patients with preoperative stiffness treated by MUA alone and those without stiffness. Methods: This retrospective study included 322 patients who underwent ARCR for full-thickness tears between January 2012 and May 2022 with a minimum 2 years of follow-up. Clinical outcomes—including passive range of motion (ROM); the Japanese Orthopedic Association (JOA) score; and the University of California, Los Angeles (UCLA) score—were assessed preoperatively and at 3, 6, 12, and 24 months postoperatively. Patients were divided into the stiffness group (MUA completed) and the non-stiffness group. Retears were evaluated using magnetic resonance imaging at 6 months postoperatively, and retear rates were analyzed by tear size (medium vs. large/massive).Results: Eighty-eight patients with stiffness and 234 without stiffness met the study inclusion criteria. Preoperative ROM, JOA, and UCLA scores were significantly lower in the stiffness group. Both groups showed significant improvements at final follow-up, with greater gains in the stiffness group. Final outcomes were comparable, except for external rotation. In medium-sized tears, the retear rate was significantly lower in the stiffness group (1.9%) than in the non-stiffness group (10.8%) (P=0.042). No significant difference was observed for large/massive tears.Conclusions: Patients with preoperative stiffness treated with MUA alone achieved comparable outcomes to those without stiffness, with improved tendon healing in medium-sized tears.Level of evidence: III. KCI Citation Count: 0